Nature and function of the Roman structures excavated at the archaeological site of Apollonia, Israel. - Rech, Raquel (Revista do Museu de Arqueologia e Etnologia, 2003)
This paper presents the nucleus of our Master research in which we tried to make and essay of interpretation about the form and function of the Roman structures of Apollonia excavated in joint expeditions between the Israeli and the Brazilian team of Apollonia Project.